Watershed Management a Tool to Address Climate Change - Sthapit, Keshar Man (The Initiation, 2010)
Climate change and its effects on the water resources therefore also, livelihood is a major global concern. Water scarcity is already a major problem for the world poor, and changes in rainfall and temperature associated with climate change will likely make this worse. This indicates that efficient and effective management of the available water becomes essential for overall development, improving livelihoods and maintaining food sufficiency. Watershed management carries number of activities managing water resource to address the ever increasing water resource problems. Therefore, watershed management could be one of the tools to cope with climate change managing scarce water resource. This paper describes some of the watershed activities dealing with water resource management. Key Words: Watershed management, Climate change, Run off, Degraded land rehabilitation DOI: 10.3126/init.v2i1.2526 The Initiation Vol.2(1) 2008 pp33